ISLPED'06 Proceedings of the 2006 International Symposium on Low Power Electronics and Design 2006
DOI: 10.1109/lpe.2006.4271799
|View full text |Cite
|
Sign up to set email alerts
|

Variation-Driven Device Sizing for Minimum Energy Sub-threshold Circuits

Abstract: Sub-threshold operation is a compelling approach for energyconstrained applications, but increased sensitivity to variation must be mitigated. We explore variability metrics and the variation sensitivity of stacked device topologies. We show that upsizing is necessary to achieve robustness at reduced voltages and propose a design methodology to meet yield constraints. The need for upsizing imposes an energy overhead, influencing the optimal supply voltage to minimize energy. Finally, we characterize performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…Due to the higher switching of the gates the optimal voltage occurs at a much low voltage for the CS adder because the leakage energy is reduced and an improvement in overall energy is achieved. It should be noted that in designing the adders only two input gates with fan-out limited to three and minimum sized transistors were employed in order to reduce leakage energy and to avoid circuit failure [9]. …”
Section: Minimum Energy Point Analysis Of Addersmentioning
confidence: 99%
“…Due to the higher switching of the gates the optimal voltage occurs at a much low voltage for the CS adder because the leakage energy is reduced and an improvement in overall energy is achieved. It should be noted that in designing the adders only two input gates with fan-out limited to three and minimum sized transistors were employed in order to reduce leakage energy and to avoid circuit failure [9]. …”
Section: Minimum Energy Point Analysis Of Addersmentioning
confidence: 99%
“…Thus, circuits need to be checked for failure rates while operating at extremely low voltages. In this paper the static noise margin (SNM) failure rates of the gates are extracted from 5k-point Monte Carlo analysis, which follows the methodology in [7]. It is found that the supply voltage value which realizes operation with less than 0.001 failure rate for a 65 nm process is 0.25V and this value is taken as the minimum reliable operating voltage (ROV).…”
Section: Sub-v T Operation Modementioning
confidence: 99%
“…More and more systems with low performance requirements are operated from a near/sub-threshold supply voltage in order to save power [3][4][5][6][7]. However, due to the fact that the gate voltage drive of the transistors operating in the sub-threshold domain is small, standard logic cells become more sensitive to process variations.…”
Section: Introductionmentioning
confidence: 99%